The Citizenship Gap in European Societies: Conceptualizing, Measuring and Comparing 'Migration Neutrality' across the EU. (6th October 2016) - Recchi, Ettore
Abstract: Equality in life‐chances of nationals and immigrants is a sensitive issue on which there is more debate than systematic evidence. To evaluate this condition across European societies, the concept of integration as "migration neutrality" is introduced. "Migration neutrality" is defined as the irrelevance of national citizenship as a predictor of key social attainments. Odds ratios are used to measure the relative risk of non‐national as compared with national citizens in the attainment of relevant resources. While this indicator cannot control for compositional differences in the populations at stake, it represents a straightforward benchmark that can be used in different domains to describe and compare foreign citizens' position relative to nationals. In this article, we calculate it across EU member states through Eurostat data. In particular, the focus is on migration neutrality in the risk of social exclusion. Country variations are found to be hardly amenable to established classifications of integration types. Moreover, the relationship between "migration neutrality" levels and pro‐immigrant policies (as measured by the Mipex index) is found to be weak, suggesting that these policies do not consistently target the reduction of the gap between nationals and non nationals.